2019
DOI: 10.5194/gmd-12-3609-2019
|View full text |Cite
|
Sign up to set email alerts
|

The global aerosol–climate model ECHAM6.3–HAM2.3 – Part 2: Cloud evaluation, aerosol radiative forcing, and climate sensitivity

Abstract: Abstract. The global aerosol–climate model ECHAM6.3–HAM2.3 (E63H23) as well as the previous model versions ECHAM5.5–HAM2.0 (E55H20) and ECHAM6.1–HAM2.2 (E61H22) are evaluated using global observational datasets for clouds and precipitation. In E63H23, the amount of low clouds, the liquid and ice water path, and cloud radiative effects are more realistic than in previous model versions. E63H23 has a more physically based aerosol activation scheme, improvements in the cloud cover scheme, changes in the detrainme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 109 publications
2
96
1
Order By: Relevance
“…Overall, nine coupled ocean-atmosphere climate models performed the SSP3-7.0 and SSP3-7.0-lowNTCF simulations, including CNRM-ESM2-1 (Séférian et al, 2019;Michou et al, 2019), MIROC6 (Takemura et al, 2005(Takemura et al, , 2009Tatebe et al, 2019), MPI-ESM1-2-HAM (Mauritsen et al, 2019;Neubauer et al, 2019;Tegen et al, 2019), NorESM2-LM (Seland et al, 2020), BCC-ESM1 (Wu et al, 2019(Wu et al, , 2020, GFDL-ESM4 (John et al, 2018;Horowitz et al, 2018;Dunne et al, 2020;Horowitz et al, 2020), CESM2-WACCM (Emmons et al, 2020;Gettelman et al, 2019;Tilmes et al, 2019), UKESM1-0-LL (Sellar et al, 2019), and MRI-ESM2-0 (Yukimoto et al, 2019). However, the first four models (CNRM-ESM2-1, MIROC6, MPI-ESM1-2-HAM, NorESM2-LM) lack interactive tropospheric chemistry schemes and therefore include identical ozone evolution in both SSP3-7.0 and SSP3-7.0-lowNTCF simulations (as recommended by AerChemMIP).…”
Section: Aerchemmip Modelsmentioning
confidence: 99%
“…Overall, nine coupled ocean-atmosphere climate models performed the SSP3-7.0 and SSP3-7.0-lowNTCF simulations, including CNRM-ESM2-1 (Séférian et al, 2019;Michou et al, 2019), MIROC6 (Takemura et al, 2005(Takemura et al, , 2009Tatebe et al, 2019), MPI-ESM1-2-HAM (Mauritsen et al, 2019;Neubauer et al, 2019;Tegen et al, 2019), NorESM2-LM (Seland et al, 2020), BCC-ESM1 (Wu et al, 2019(Wu et al, , 2020, GFDL-ESM4 (John et al, 2018;Horowitz et al, 2018;Dunne et al, 2020;Horowitz et al, 2020), CESM2-WACCM (Emmons et al, 2020;Gettelman et al, 2019;Tilmes et al, 2019), UKESM1-0-LL (Sellar et al, 2019), and MRI-ESM2-0 (Yukimoto et al, 2019). However, the first four models (CNRM-ESM2-1, MIROC6, MPI-ESM1-2-HAM, NorESM2-LM) lack interactive tropospheric chemistry schemes and therefore include identical ozone evolution in both SSP3-7.0 and SSP3-7.0-lowNTCF simulations (as recommended by AerChemMIP).…”
Section: Aerchemmip Modelsmentioning
confidence: 99%
“…Eight coupled ocean-atmosphere climate models performed the SSP3-7.0 and SSP3-7.0-lowNTCF simulations, including 110 CNRM-ESM2-1 (Séférian et al, 2019;Michou et al, 2019), MIROC6 (Takemura et al, 2005(Takemura et al, , 2009Tatebe et al, 2019), MPI-ESM1-2-HAM (Mauritsen et al, 2019;Neubauer et al, 2019;Tegen et al, 2019), BCC-ESM1 (Wu et al, 2019, submitted), In prep. ;Horowitz and et al,In prep.…”
Section: Aerchemmip Modelsmentioning
confidence: 99%
“…Also, Kulkarni et al (2016) analyzed the ice formation ability of diesel soot under cirrus conditions and reported a 1 % frozen fraction of the soot particles at similar ice saturation ratios. Nichman et al (2019) examined six types of BC particles considered as proxies for atmospheric BC and found onset saturation thresholds for ice nucleation between 1.1 and 1.5. Recent studies observed BC nucleation at cirrus temperatures but explained it with pore condensation and freezing rather than with deposition nucleation (Wagner et al, 2016;Marcolli, 2017;Mahrt et al, 2018;David et al, 2019).…”
Section: Introductionmentioning
confidence: 99%